MAIN TRENDS OF FRENCH LITERATURE OF THE 17TH CENTURY AND THEIR INFLUENCE ON EUROPEAN LITERATURE - Radjabov Ruslan Radjabmurodovich; Karimova Maftuna Ismat kizi (Western European Studies, 2025)
The article discusses the main trends, poetry and styles of French literature of the 17th century, as well as the influence of French poetry on European literature. Examples are given of how the ideas of classicism, baroque and precision literature played an important role in the development of literature in other countries. The poems created during this period are distinguished by clarity, logic, order and measure, served as an example for subsequent generations and retained their value
Keywords: Baroque poetry; classicism; tragedy